A Novel Perspective of a Laguerre–Gaussian Beam's Phase Acceleration in Chiral Medium by Using Distinguishability Property - Francisco E. Alban-Chacon; Arturo Pazmino; Peter Iza; Manuel S. Alvarez-Alvarado; Erick A. Lamilla-Rubio (IEEE Photonics Journal, 2023)
The concept of orbital angular momentum has gained significant interest in recent years across various fields of science, particularly in physics and biology. In this article, we present a novel approach to investigating the acceleration and deceleration of the phase distribution of a Laguerre–Gaussian beam. Our model proposes a topological transformation from a canonical vortex to a non-canonical vortex when the beam interacts with a chiral medium, based on a generalized distinguishability property of the vortex. We compare our model's predictions with phase acceleration data from simulations by Liu et al., showing excellent agreement. Additionally, we provide a quantum mechanical interpretation of our model. Our results show that the elliptical beam resulting from passing through a slab of chiral media is a superposition of various LG modes of the topological charge $l$ . We conclude that the distinguishability property of a canonical vortex beam, where $ω \propto \frac{1}{l}$ , holds physical significance and practical relevance.